Reactive Power Compensation Capacity Optimization Method Based on BSSSO Algorithm - Shenglong QI; Lei LI; Yupeng HE; Lin ZHU; Fang WANG; Hongbo ZOU (Zhongguo dianli)
The objective of reactive compensation capacity is to minimize the active power loss and take into account the voltage balance. Firstly, according to the actual optimization of reactive power compensation capacity, a multi-objective reactive power compensation capacity optimization model considering active power loss, voltage deviation and voltage stability was established. Then, a BSSSO algorithm based on bird swarm algorithm (BSA) and shuffled shepherd optimization algorithm (SSOA) is proposed to optimize reactive power compensation capacity. Finally, the proposed method is verified by a simulation example, and the results show that the proposed method has superior performance and can take into account the balance of all indexes.